To What Extent Do Successive Cohorts Adopt Different Publication Patterns? Peer Review, Language Use, and Publication Types in the Social Sciences and Humanities - Guns, Raf; Eykens, Joshua; Engels, Tim C. E. (Frontiers in Research Metrics and Analytics, 2019)
This article presents a cohort analysis to study changes in the publication patterns of scholars working at a social sciences and humanities (SSH) university department or research unit in Flanders, Belgium. Starting from a comprehensive bibliographic database, we analyze the peer review status, publication language, publication type (journal article, book publication, or proceedings), and coverage in Web of Science (WoS) for publications produced between 2000 and 2014. Through a cohort analysis of the authors, a distinction can be made between effects that reflect changes in the characteristics of how researchers of comparable seniority publish (intracohort change) and effects that are due to the disappearance of researchers and/or introduction of new researchers (cohort succession). Our findings indicate that there is a trend across all five cohorts and in both the social sciences and humanities toward peer review, use of English, and publishing in WoS-indexed journals. While we witness clear intracohort changes, cohort succession effects are shown to be much weaker. The oldest cohort appears to maintain a traditional SSH profile, with lower shares of peer-reviewed publications, publications in English, journal articles, and publications indexed in WoS. As for publication types, all cohorts exhibit a slightly declining share of journal articles over time in favor of book publications, particularly in the humanities. The study shows that cohort analysis is a useful instrument to gain better insight into the evolution of publication patterns.